The relationship between the neutrophil–lymphocyte ratio and the coronary collateral circulation in patients with chronic total occlusion. (July 2014) - Kalkan, ME; Şahin, M; Kalkan, AK; Güler, A; Taş, MH; Bulut, M; Demir, S; Acar, RD; Arslantaş, U; Öztürkeri, B; Güler, Y; Akçakoyun, M
Objectives: Previous studies showed the association between the major adverse cardiovascular outcomes and both higher neutrophil and lower lymphocyte counts. We aimed to investigate whether there is an association between the neutrophil-lymphocyte ratio (NLR) value and the development of coronary collateral circulation (CCC) in patients with coronary chronic total occlusion (CTO). Methods: A total of 274 patients with CTO were included in this study. Patients were then classified according to their Rentrop collateral grades as either poor (Rentrop grades 0-1) or good (Rentrop grades 2-3). Clinical information and analyses of blood samples were obtained from a review of the patients' charts. Results: Although there was no difference between the two groups with regard to cardiovascular risk profiles, the NLR values were significantly higher in the patients who had poorly developed CCC (2.6 ± 0.5 vs 2.2 ± 0.4, p<0.001). NLR, high-sensitivity C-reactive protein (hs-CRP), white blood cell count (WBC), age, diabetes, fasting glucose levels and body mass index were found to have univariate association with poorly developed CCC (p<0.1). In a multivariate logistic regression model, NLR (odds ratio 1.88, 95% confidence interval (CI) 1.37–2.74; p<0.001), high-sensitivity C-reactive protein and WBC were found to be the independent predictors of poor CCC. In receiver operator characteristic curve analysis, the optimal cut-off value of NLR to predict poor CCC was found as 2.17, with 77% sensitivity and 65% specificity. Conclusion: NLR, as a novel cardiovascular risk marker, is an important, simple and inexpensive method which can be used by the cardiologist as a screening inflammation tool to estimate the development of CCC in patients with CTO.